Success of TPM concept in a manufacturing unit – a case study. Issue 3 (5th March 2018) - Singh, Jagdeep; Singh, Harwinder; Sharma, Vinayak
Abstract : Purpose: The purpose of this paper is to implement new concept of mobile maintenance in manufacturing industry of Northern India. This study tries to introduce the new concept of total productive maintenance program in the case company. Design/methodology/approach: The approach is to study the role of mobile maintenance in the context of Indian industry through significant improvement in overall equipment effectiveness (OEE). Findings: This industry adopted the mobile maintenance strategy and improved their productivity by decreasing breakdown time. This mobile maintenance strategy can reduce major breakdowns, setup and adjustment losses and improve productivity, product quality and OEE of equipment. Results indicate an average increase in production of 15.63 percent, average reduction in breakdown time of 23.14 percent, average reduction in rejection rate of 17.94 percent and average increase in OEE of 17.08 percent. Moreover, the results of improvements in parameters are validated by using multi-criteria decision-making approaches. Research limitations/implications: Maintenance is of great importance in modern era of manufacturing systems for those organizations who consider maintenance as a profit-generating factor. In the dynamic and highly challenging environment, reliable manufacturing equipment is regarded as the major contributor to the performance and profitability of manufacturing systems. Moreover, the selection of manufacturing industry is done on the basis of convenience sampling technique. Originality/value: Industry can improve machine availability and OEE by implementing this mobile maintenance concept especially in the Indian context and is very beneficially for the case company under study.